Mitigating Online Gambling through Pancasila Education and the Strengthening of Digital-Financial Literacy: A Phenomenological Study - Ridhoh, M. Yunasri; Bakhtiar, Bakhtiar; Randiawan, Randiawan (Actual Insight, 2025)
This study aims to explore how the integration of digital literacy and financial literacy into the Pancasila education course can foster students' digital-financial intelligence in addressing the negative impacts of online gambling. Employing a phenomenological approach, the research delves into students' lived experiences related to online gambling addiction. The findings reveal several key points: (1) students’ encounters with online gambling are significantly influenced by a lack of financial literacy, digital literacy, and moral resilience; (2) both digital and financial literacy play crucial roles in mitigating this issue by cultivating digital-financial intelligence; (3) the integration of digital and financial literacy into Pancasila education has proven effective in shaping students’ digital-financial awareness and guiding them to recognize the dangers of online gambling, manage their finances wisely, and behave ethically in alignment with Pancasila values; (4) furthermore, the development of a more practical and contextually relevant curriculum is vital for sustainably addressing this issue; and (5) the study strongly recommends a deeper integration of digital and financial literacy within the Pancasila education curriculum, along with the inclusion of materials that are relevant to the current digital social phenomena faced by students. Through this approach, students will be better equipped to navigate the digital world with wisdom, responsibility, and ethical awareness.